2023
DOI: 10.1021/jacs.3c07070
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated Radical Pairs in Organic Synthesis

Minsoo Ju,
Zhipeng Lu,
Luiz F. T. Novaes
et al.

Abstract: Frustrated radical pairs (FRPs) describe the phenomenon that two distinct radicals�which would otherwise annihilate each other to form a closed-shell covalent adduct�can coexist in solution, owing to steric repulsion or weak bonding association. FRPs are typically formed via spontaneous single-electron transfer between two sterically encumbered precursors�an oxidant and a reductant�under ambient conditions. The two components of a FRP exhibit orthogonal chemical properties and can often act in cooperativity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…In order to confirm the electronic nature of the LA/LB pairs, time dependent Density Functional Theory (TD-DFT) calculations were performed at the ωB97XD 42 /6-31G(d,p) level of theory to investigate the possibility of Frustrated Radical Pairs (FRP) 43,44 formation in the studied systems. Using the simplest system with unsubstituted boron and nitrogen (H/H) as a reference, we identified an electronic transition from nitrogen to boron resulting in FRP formation with a transition energy of 95.6 kcal mol −1 (4.147 eV).…”
Section: Computational Detailsmentioning
confidence: 99%
“…In order to confirm the electronic nature of the LA/LB pairs, time dependent Density Functional Theory (TD-DFT) calculations were performed at the ωB97XD 42 /6-31G(d,p) level of theory to investigate the possibility of Frustrated Radical Pairs (FRP) 43,44 formation in the studied systems. Using the simplest system with unsubstituted boron and nitrogen (H/H) as a reference, we identified an electronic transition from nitrogen to boron resulting in FRP formation with a transition energy of 95.6 kcal mol −1 (4.147 eV).…”
Section: Computational Detailsmentioning
confidence: 99%
“…166 Tris(pentafluorophenyl)borane can also exhibit radical activity within the chemistry of frustrated Lewis pairs (FLP). 229,230 In 2020, Ooi and co-workers described a catalytic application of B(C 6 F 5 ) 3 towards a C-C bond formation between N,N-dialkylamines and Michael acceptors (Scheme 102). 231 The reaction of a-silyl substituted amine 102.1 with methyl vinyl ketone 102.2 proceeded in ether/methanol mixture with catalytic amounts of the borane in the absence of irradiation, and the corresponding product 102.3 was isolated with 92% yield.…”
Section: Polyfluoroarenes As Catalysts and Initiatorsmentioning
confidence: 99%
“…That same year, Wang et al also reported single electron oxidation of a methylene-bridged triphenylamine by B­(C 6 F 5 ) 3 . In later studies, phosphine-coordinated boryl radicals were developed and characterized, including the observation of a Lewis basic radical cation (R 3 P•+) by Stephan et al and the [B­(C 6 F 5 ) 3 ]•– radical anion by Slootweg et al (Scheme b). Müller et al also spectroscopically observed the SET between B­(C 6 F 5 ) 3 and bespoke LBs (Scheme c,d). , This fundamental understanding has recently been extended to radical-assisted catalysis. Besides these findings, Meijer et al also extended FRP into supramolecular chain structure by small molecular boranes and amines, with photoinduced SET between LA and LB observed (Scheme e). , Most recently, Lin et al reported the FRP-mediated regioselective C–H functionalization using the neutral [HMDS • /HPDS • / t BuO • ] [TEMPO • ] pair. , …”
Section: Introductionmentioning
confidence: 97%